Third-Party Interest Rate Spread Determinant of Bank in Indonesia - Suyasa, I Ketut; Manurung, Adler; Usman, Bahtiar (International Journal of Economic Research and Financial Accounting, 2025)
This research examines the determinants of the banks’ third-party interest rate spread. The dependent variable of this research is the banks’ third-party interest rate spread. Independent variables include the bank-specific, macroeconomic, and global condition factors. The bank-specific factors include capital adequacy, unresolved credit, corporate value, operational inefficiency, non-interest income portion, and stocks’ total risk. The reference interest rate and saving propensity are part of macroeconomic factors. The global condition factor uses the COVID-19 pandemic as a dummy variable. The mediating variable uses the banks’ customer trust. The banks’ customer trust consists of depositor trust and debtor trust. The research uses panel data from banks' annual reports, the Indonesian Central Bank (Bank Indonesia), Indonesia's Central Bureau of Statistics (Badan Pusat Statistik), and Yahoo Finance from 2010 to 2022. According to the panel selection and classical test, the Generalize Leases Square Fix Effect Model was chosen for panel data estimation. This research found that unresolved credit, operational inefficiency, and saving propensity significantly affect depositor trust. Unresolved credit, operational inefficiency, saving propensity, and the COVID-19 pandemic significantly affect debtor trust. Capital adequacy, operational inefficiency, saving propensity, stocks’ total risk, the COVID-19 pandemic, depositor trust, and debtor trust significantly affect the third-party interest rate spread. Depositor trust and debtor trust as mediating variables successfully mediated some of the independent variables to influence third-party interest rate spread.